Design of Smart Iron Plate Heating Machine Using Quality Function Deployment Method - Raden Rara Arsia Permata Noor; Berlianty, Intan (Universitas Negeri Gorontalo, 2025)
The number of gloves entering the ironing department is greater than the number of gloves that are ironed, causing a lot of accumulation of gloves that have not been ironed. Based on this problem, a problem identification was carried out using the IDEF0 method. Based on the results of the discussion, the solution to the existing problem is to design an ironing plate heating machine using the Quality Function Deployment (QFD) method which can reduce ironing process time and increase productivity. After the machine was completed, a test was carried out where the results of the gloves from the ironing plate heating machine had met the standard operating procedure. In addition, the standard ironing time decreased where initially when using a conventional iron it took 47.68 seconds to iron. While when using an ironing plate heating machine it took 36.14 seconds to iron. The number of gloves produced in 4 hours of using a conventional ironing machine produced 300 gloves while the ironing plate heating machine produced 350 gloves.